2021
DOI: 10.1140/epjc/s10052-021-09916-w
|View full text |Cite
|
Sign up to set email alerts
|

Strange hidden-charm tetraquarks in constituent quark model

Abstract: In the framework of the chiral quark model (ChQM), we systematically investigate the strange hidden-charm tetraquark systems $$cs{\bar{c}}{\bar{u}}$$ c s c ¯ u … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…More recently, the LHCb Collaboration reported two charmonium-like states with strangeness , named Z cs (4000) + and Z cs (4220) + , in the J/ψK invariant mass spectrum [55], where the mass of the former one is similar to the one of Z cs (3985) observed by BESIII Collaboration. Similar to the case of Z b (10610) and Z c (3900)/Z c (3885), the observed masses of Z cs (3985)/Z cs (4000) are close to the threshold of D * s D, the properties of Z cs (3985)/Z cs (4000) have been investigated in molecular [56][57][58][59][60][61][62][63][64][65][66] and tetraquark [67][68][69][70][71][72] scenarios.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…More recently, the LHCb Collaboration reported two charmonium-like states with strangeness , named Z cs (4000) + and Z cs (4220) + , in the J/ψK invariant mass spectrum [55], where the mass of the former one is similar to the one of Z cs (3985) observed by BESIII Collaboration. Similar to the case of Z b (10610) and Z c (3900)/Z c (3885), the observed masses of Z cs (3985)/Z cs (4000) are close to the threshold of D * s D, the properties of Z cs (3985)/Z cs (4000) have been investigated in molecular [56][57][58][59][60][61][62][63][64][65][66] and tetraquark [67][68][69][70][71][72] scenarios.…”
Section: Introductionmentioning
confidence: 63%
“…In Ref. [69], we investigate the Z cs in the chiral quark model (ChQM) and we find a resonance state with J P = 0 + , the energy of which is close to the one of Z cs (3985). Besides, two more new resonances were predicated in the vicinity of 4410 MeV, with J P = 0 + and J P = 1 + , respectively, which could be tested by further experiments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Ref. [9], the diquark-antidiquark [cs][cn] configurations have been investigated, and it's found that there would be resonance states falling in the mass range of 3916.5 ∼ 3964.6 MeV with quantum numbers J P = 0 + , and 4008.8 ∼ 4091.2 MeV with J P = 1 + . Thus, one may conclude that a compact tetraquark state with J P = 0 + or J P = 1 + may take considerable probability in Z cs (3985).…”
Section: B Zc and Zcs Statesmentioning
confidence: 99%
“…The typical mesonic exotic states, such as the charmonium-like state Z c (3900) ± observed in the π ± J/ψ invariant mass spectra of the process e + e − → π + π − J/ψ [3] and the Z cs (3985) state observed in the D − s D * 0 and D * − s D 0 final states of the e + e − → K + D − s D * 0 (D * − s D 0 ) reaction [4], may contain at least four ccq q quarks. Theoretically, the exotic meson states can be explained as compact tetraquark states in quark potential model [5][6][7][8][9][10][11], QCD sum rule [12][13][14][15], and diquark-diquark picture [16,17]. While, they could be also described as the molecular states in effective field theory [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [58][59][60][61][62][63][64][65][66]. An analysis of the D * 0 Ds +D 0 D * s invariant mass spectra was performed in Ref.…”
Section: Introductionmentioning
confidence: 99%